Role Regulation In Guard Stability Financial System In Indonesia: A Study Of The Authorities Service Finance (Ojk) And Challenge Digital Financial Sector - Rico Nur Ilham; Irada Sinta; Frengki Putra Ramansyah; Mita Darmayanti; Nurul Hidayati (CV. RADJA PUBLIKA, 2025)
Regulation in the financial industry plays a crucial role in maintaining financial system stability, protecting consumers, and ensuring the continued and transparent operation of financial institutions. This study aims to examine the role and effectiveness of regulation in the Indonesian financial industry, with a particular focus on the role of the Financial Services Authority (OJK) in overseeing and developing the financial sector, including the digital financial sector. Through an in-depth literature review, this study seeks to provide insight into how implemented regulations can support financial sector growth while addressing challenges arising from the development of financial technology. The findings of this study are expected to provide more effective policy recommendations to support sustainable financial system stability.